Compound Formation in Language Mixing - Alexiadou, Artemis (Frontiers in Psychology, 2020)
In this paper, I discuss nominal compound formation in language contact situations, the question being of how compounding in language mixing can inform both theories of mixing and theories of word-hood. This contributes to our further understanding of how word formation operates in cases of language mixing and what exactly is being mixed in mixing, i.e., words vs. units smaller than words, e.g., stems or roots. Compounding is important to answer this question, as languages differ with respect to the units they employ for compound formation, i.e., phrases vs. stems. The data to be discussed will be a mixture of materials that have already been published in the literature and newly collected data and involve several mixing varieties, namely, Greek–English, Greek–Italian, Greek–Turkish, Turkish–Norwegian, Turkish–Dutch, and French–Dutch. I then offer an analysis using the tools of syntactic models of word formation (e.g., distributed morphology), assuming a decompositional approach.